Bouchra Khalili: Between Circles and Constellations - Khalili, Bouchra (Sharjah Art Foundation, Sharjah, United Arab Emirates, 2024)
Bouchra Khalili: Between Circles and Constellations catalogues the eponymous exhibition at Sharjah Art Foundation (7 September–1 December 2024), following its debut at Museu d’Art Contemporani de Barcelona (MACBA) (17 February–21 May 2023). The book, published in conjunction with the exhibition, explores the artist’s 15-year engagement with anti-colonial struggles and post-colonial histories of liberation and solidarity, intertwining historical narratives and lived experiences to highlight the political agency of those marginalised by the nation-state’s exclusionary models of citizenship. Originally published in 2023 by MACBA and the Foundation, this new edition features an Arabic translation that foregrounds the importance of language in Khalili’s practice and extends the reach of her critical inquiries to new audiences. It also documents her most recent two-channel film installation The Public Storyteller (2024), which, co-produced with Kunstenfestivaldesarts, explores the resonance of al halqa [circle]—an ancient Morocccan form of public storytelling—within diasporic political movements, connecting North African and transnational communities through performances that transcend territorial boundaries. The publication includes a foreword by the show’s curator Hoor Al Qasimi, Sharjah Art Foundation President and Director, and features essays by KJ Abudu, Omar Berrada, Övül Ö Durmusoglu, Elvira Dyangani Ose, Olivia C Harrison, Yousef Rocé Kamisky and Bouchra Khalili. Bringing together commissioned texts, interviews, archival material and insights into the artist’s creative process, the book offers a multimodal narrative that encourages the public to reconsider civic engagement outside the framework of the nation-state.